Strengthening Business Management through the Digitalization of Simple Financial Statements and Brand Development for UMKM and Bumdes in Cipayung Village, Bogor District - Abdullah Zamasari; Susy Hambani; Didi; Edi Priyono; Fadilla Syahrani; Alfiyah Khanza; Andini Rahmawati; Assyifa Melani; Falsa Mulia; Hendriyan Taofik; Sendy Pratama (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pengabdian Kepada Masyarakat (PKM) was held in Cipayung Village, Megamendung District, Bogor Regency. The objects of these programs are UMKM and BUMDes in Cipayung Village which have very good potential in terms of location and market share, but are still experiencing various problems. The problems faced by UMKM and Cipayung BUMDes are a lack of knowledge regarding the importance of developing branding or business identity for their business, not recording financial reports properly and still manual financial bookkeeping carried out by BUMDes. Based on these problems, we will carry out various work programs including training and assistance in preparing simple financial reports for MSMEs, digitizing financial accounting for BUMDes and developing branding for MSMEs in Cipayung Village. With several work programs that have been implemented, it is expected to improve the quality and performance of MSMEs in Cipayung Village in terms of business management and business management by increasing knowledge and skills regarding simple financial reports and developing branding or business identity. Likewise, the Cipayung BUMDes are expected to be able to improve and improve their business management in terms of efficiency and effectiveness of bookkeeping with the digitalization of financial accounting that has been realized.